Impact of Macro-economic Variables on Stock Price on Nepal Stock Exchange - Pokharel, Shiva Prasad; Pokhrel, Bishnu Prasad (Cognition, 2021)
The purpose of this study is to investigate the relationship between macroeconomic variables and stock prices in Nepal Stock Exchange (NEPSE) Nepal. To find the impact of macroeconomic variables on stock price the analytical research is conducted. Secondary data were used in this study and the study considers annual data of several macroeconomic variables from 2001 to 2018. Stock price is considered as dependent variable and gross domestic product, exports, consumer price index, money supply, exchange rate, foreign direct investment and oil prices are treated as independent variable. The stationary of data is checked through Augmented Dickey Fuller test. All variables are stationary at zero lag. For the statistical result, descriptive statistics, correlation and, multiple regression analysis are used. The overall results revealed that oil price and money supply have significant positive impact on the stock price while other variables have adversely affects the stock price.